Screening and Validation of Reference Genes for RT-qPCR Under Different Honey Bee Viral Infections and dsRNA Treatment - Deng, Yanchun; Zhao, Hongxia; Yang, Sa; Zhang, Li; Zhang, Lina; Hou, Chunsheng (Frontiers in Microbiology, 2020)
Honey bee viruses are one of the most important pathogens that have contributed to the decrease in honey bee colony health. To analyze the infection dynamics of honey bee viruses, quantification of viral gene expression by qPCR is necessary. However, suitable reference genes have not been reported from viral and RNAi studies of honey bee. Here, we evaluated the expression of 11 common reference genes (ache2, rps18, β-actin, tbp, tif, rpl32, gadph, ubc, α-tubulin, rpl14, and rpsa) from Apis mellifera (Am) and Apis cerana (Ac) under Israeli acute paralysis virus (IAPV), chronic bee paralysis virus (CBPV), and Chinese sacbrood virus (CSBV) infection as well as dsRNA-PGRP-SA treatment, and we confirmed their validation by evaluating the levels of the defensin 1 and prophenoloxidase (ppo) genes during viral infection. Our results showed that the expression of selected genes varied under different viral infections. ache2, rps18, β-actin, tbp and tif can be used to normalize expression levels in Apis mellifera under IAPV infection, while the combination of actin and tif is suitable for CBPV-infected experiments. The combination of rpl14, tif, rpsa, ubc, and ache2 as well as more reference genes is suitable for CSBV treatment in Apis cerana. Rpl14, tif, rps18, ubc and α-tubulin were the most stable reference genes under dsRNA treatment in Apis mellifera. Furthermore, the geNorm and NormFinder algorithms showed that tif was the best suitable reference gene for these four treatments. This study screened and validated suitable reference genes for the quantification of viral levels in honey bee, as well as for RNAi experiments.